Trends in Religious-Based School Selection: Analysis of Parental Motivation - Sri Haryati; Sukarno Sukarno; Siswanto Siswanto; Eli Trisnowati (AL-ISHLAH: Jurnal Pendidikan, 2024)
The rise in parents choosing religion-based schools, specifically Islamic schools, reflects a trend warranting further investigation to inform educational policy and school management. Understanding the motivations driving these choices is essential to align educational practices with parental expectations. This study utilized a quantitative survey approach, sampling 126 parents from various Islamic schools in (region or demographics). A 47-item questionnaire assessed intrinsic motivations (e.g., desire for religious knowledge, moral development, academic performance) and extrinsic motivations (e.g., school environment, curriculum, regulations). Findings reveal that the primary intrinsic motivation among parents is fostering noble morals in their children, while the leading extrinsic factor is the presence of well-defined school regulations. Additional factors, including the quality of religious instruction and alignment with the school’s vision and mission, also significantly influence parental decisions. These results highlight critical motivational patterns among parents that shape their educational choices, suggesting that both intrinsic and extrinsic motivations are pivotal. Understanding these factors provides actionable insights for administrators and policymakers to adapt school offerings to meet parental expectations. This study contributes to the limited literature on motivations for choosing religion-based education, offering practical implications for Islamic school administration and policy formulation aimed at enhancing educational outcomes through alignment with family priorities.